Screening of Pulmonary Tuberculosis in Household Contacts With Acid Fast Bacteria (AFB) Positive Pulmonary Tuberculosis Patients in Ciwangi Village, Balubur Limbangan Subdistrict, Garut District - Shinta Nuriah; Undang Ruhimat; Rivana Aryadi; Rahayu Nirmatul Mutmainah (LPPM STIKes Muhammadiyah Ciamis, 2023)
Background & Objective Tuberculosis is an infectious disease caused by acid-fast bacteria, namely Mycobacterium tuberculosis, which mainly attacks the lungs. Pulmonary tuberculosis is a global health problem with the second deadliest case after HIV/AIDS infection, and ranks third with the most TB cases after India and China. The main source of transmission is patients with active TB pulmonary tuberculosis who can transmit to people around them. This study aims to determine whether pulmonary TB transmission occurs in people who are in household contact with patients with acid-fast bacteria pulmonary TB active. Method This study is descriptive, using the Ziehl neelsen examination method, with a total sampling technique, conducted on 34 people who are in household contact with pulmonary TB patients in Ciwangi Village, Balubur District, Limbangan. Result Based on the examination results in people who are in contact with people with TB, the results are negative, the presence of the bacteria that cause TB. Conclusion The results of Pulmonary Tuberculosis screening conducted on 34 people from 13 heads of families, it can be concluded that the results of TB microscopy with the Ziehl neelsen technique were negative.